Proceedings of the Ocean Drilling Program, 148 Scientific Results 1996
DOI: 10.2973/odp.proc.sr.148.130.1996
|View full text |Cite
|
Sign up to set email alerts
|

Data Report: Magnetic Properties and Magnetic Oxide Mineralogy of Upper Crustal Rocks from Holes 504B and 896A

Abstract: We present the results of studies of magnetic mineralogy and magnetic properties of Holes 504B and 896A upper crustal rocks recovered during Leg 148. The ratio of saturation remanence to saturation magnetization (J RS /J S ) ranges from 0.012 to 0.154 (mean = 0.06) in samples from Hole 504B, consistent with pseudo-single-domain behavior. Hole 896A samples display a variable ratio of J RS /J S that ranges from 0.012 to 0.154 (mean = 0.076), reflecting the differences in grain morphologies and magnetic propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…They found that the degree of deuteric oxidation increases with increasing depth and suggested that the higher degree of oxidation is due to a slower cooling rate of the deeper sheeted dike basalts. Therefore hightemperature oxidation is apparently a common subsolidus process affecting the titanomagnetite in the lower sheeted dikes at Hole 504B (down to 2100 m bsf for Leg 148 samples [Stokking et al, 1996] ............................ alteration are therefore key processes in subsolidus evolution and modification of titanomagnetite and account for the properties of the magnetic carrier in the sheeted dike basalts. The primary titanomagnetite in the upper sheeted dike basalts may appear to be homogeneous when observed with reflectedlight microsopy and even SEM or EMPA, even though it has been subjected to pervasive subsolidus oxidation and exsolution.…”
Section: Features Including Mineral Assemblages Compositions and Imentioning
confidence: 99%
“…They found that the degree of deuteric oxidation increases with increasing depth and suggested that the higher degree of oxidation is due to a slower cooling rate of the deeper sheeted dike basalts. Therefore hightemperature oxidation is apparently a common subsolidus process affecting the titanomagnetite in the lower sheeted dikes at Hole 504B (down to 2100 m bsf for Leg 148 samples [Stokking et al, 1996] ............................ alteration are therefore key processes in subsolidus evolution and modification of titanomagnetite and account for the properties of the magnetic carrier in the sheeted dike basalts. The primary titanomagnetite in the upper sheeted dike basalts may appear to be homogeneous when observed with reflectedlight microsopy and even SEM or EMPA, even though it has been subjected to pervasive subsolidus oxidation and exsolution.…”
Section: Features Including Mineral Assemblages Compositions and Imentioning
confidence: 99%
“…This involves the redeposition of near-pure magnetite, which is the second type of secondary magnetite, or SMII. Redeposition strongly favors nucleation on ilmenite lamellae that have survived in leached primary grains, leading in some instances to products that closely mimic and were formerly mistaken [Pariso et al, 1995;Pariso and Johnson, 1991;Stokking et al, 1996] for the magnetites containing lattices of ilmenite lamellae often produced during the initial cooling of basaltic flows and dikes [Haggerty, 1976]. The stages in the production of SMII are illustrated in Figure 1.…”
Section: Complex Of the Troodos Ophiolitementioning
confidence: 99%
“…The efficient remanent magnetization of deeper layers could have been delayed during their thermochemical history. Ocean Drilling Program (ODP) results from holes 504B [ Kinoshita et al , 1989; Pariso and Johnson , 1989; Pariso et al , 1995; Smith and Banerjee , 1986; Stokking et al , 1996; Hall and Muzzatti , 1999], 735B [ Pariso and Johnson , 1993], and 896A [ Stokking et al , 1996] have been used to lend support to the concept of the contribution of deeper crustal source layers to surface anomalies.…”
Section: Introductionmentioning
confidence: 99%